Phase morphology control and the selective localization of MWCNT for suppressing dielectric loss and enhancing the dielectric constant of HDPE/PA11/MWCNT composites. Issue 77 (2nd August 2016) - Zheng, Xiaofang; Zheng, Shaodi; Zhang, Xi; Yang, Wei; Liu, Zhengying; Yang, Mingbo
Abstract : A nanocomposite with a giant dielectric constant and suppressed dielectric loss was obtained by tailoring the selective localization of MWCNT in the PA11 phase and improving the interfacial interaction between HDPE and PA11. Abstract : A nanocomposite with a giant dielectric constant and suppressed dielectric loss was obtained from the high-density polyethylene (HDPE)/polyamide-11 (PA11)/multiwalled carbon nanotube (MWCNTs) composites, by tailoring the selective localization of MWCNTs in the PA11 phase and improving the interfacial interaction between HDPE and PA11 through the addition of high density polyethylene grafted maleic anhydride (HDPE- g -MAH). The effect of the addition of the polar component compatibilizer (HDPE- g -MAH) and PA11 on the dielectric properties of the HDPE/MWCNT composites was systematically studied. Through the addition of the polar phase (PA11) into the HDPE/MWCNT composites as the dispersed phase, with MWCNTs selectively localized in it, the dielectric properties were improved. Subsequently, as the compatibilizer (HDPE- g -MAH) was added into the HDPE/PA11/MWCNT composites, the interface between HDPE and PA11 became indistinct and PA11 in the form of dispersed phase coated MWCNTs could generate some degree of combination, to cause the size of the dispersed phase to get larger. Therefore, the dielectric constant of HDPE/PA11/MWCNT composites containing compatibilizer was up to 4000 at 3 wt% MWCNT and 10 3 Hz, which was attributed to the selective localization of MWCNTs to reduce the distance between the MWCNTs and the formation of larger sized microcapacitors (PA11 coated MWCNTs), and dielectric loss was still maintained at a low value (∼2 at 10 3 Hz), which was due to the stronger interfacial interaction between HDPE and PA11. The composites displayed advantages of excellent dielectric properties and good processability, which are suitable for the development of dielectric materials for energy storage.